Population and Home Range of Javan-hawk Eagle (Spizaetus bartelsi Stresemann, 1924) at Mount Kendeng, Cikaniki Resort, Gunung Halimun National Park - Tri Widodo; Jarwadi Budi Hernowo; Kuswandono . (Media Konservasi, 2004)
Population and home range study of javan-hawk eagle (Spizaetus Bartelsi Stresemann,  1924) was conducted from Februari 2003 until July 2003 at Mount Kendeng Cikaniki Resort (± 8.5 km2),  Gunung  Halimun  National Park,  West Java.  Indonesia.  There were  11 individu of javan-hawk eagles observed from  5 station specified as monitoring plots, consisted  of  8 adults and 3 youngs.  Individual  density of javan-hawk eagle  was about 0. 77 km2/individu.  The pairs  density  at around 2.83  km2/pairs  and sex  ratio  was close  to  1 :  1.   Javan-hawk eagle  in this  area  was distributed al Mount  Kendeng  area.  Mount Andam,  and about Nirmala tea plantation.  Habitat type in Mount Kendeng can be grouped  as a natural forest  (tropical rain forest),  border between natural forest  and tea plantation,  tea plantation,  countrifield  (resident  settlement)  and also the  agriculture form  (rice field).  The  habitat characteristics  of javan hawk eagle were as follows  :  natural forest  with high variety  of fauna  (abundance  of food sources),  hilly area,  a river stream presence,  and the natural forest can give its function as a food supply,  nesting area,  mating,  and shelter.  Home range  for Pengkeh (male adult of javan-hawk eagle) in mount Kendeng was around+ 3.06  km2,  and its pair  of Pengkeh (female  adult of javan-hawk  eagle)  was about+ 1.69  km2,  meanwhile  home  range  of Juvenex  (young  of javan-hawk eagle) was close to±  1.31  km2 and or the No Molt 2 (male adult of javan-hawk eagle) in mount Andam was about± 2./9 km2.  The hunting area for  Pengkeh was  about+ 0.31  km2, pair  of Pengkeh were   ± 0.13  km2, Juvenex was ± 0.19 km2 and/or the No Molt 2 was  about±  0.13 km2.  At the/air weather condition,  a lot of perch activity was seen al 08.30 a.m-11.00 a.m  and 11.30 a.m-02.20 p.m,  while a lot of flying activity  was seen at 08.30 a.m- 11.00 a.m and 12.00 a.m-0/.20 p.m. Keywords:  javan-hawk eagle. population,  home range,  daily activity